ITpreneurship : a new perspective on characteristics of entrepreneurs in IT industry - Ng, Hooi Ling (2014)
The current emphasis on entrepreneurship in Singapore has spurred the team into the study of this topic. The team has selected the IT industry because this newly-emerged industry commands high market potential and growth. A second motivation for the study is that Singapore is in need of entrepreneurs who can constantly innovate, experiment, fail, pick themselves up and start all-over again in this industry, which the team denotes as ITpreneurs. Such technically-equipped ITpreneurs who possess the ability to exploit opportunities and confidence to take up major challenges can play an essential role in contributing to the economic development of Singapore.